Tradisi Silaturrahmi di Kalangan Nahdiyyin Dalam Persepektif Al-quran dan Al-hadist - Moh. Muafi Bin Thohir; Abdul Ghofur (Nusantara: Indonesian Journal of Islamic Studies, 2023)
NU As an organization that is the embodiment of traditional values that have developed in society, in the historical process the Nahdliyin have succeeded in forming their own knowledge system, which is an accumulation of knowledge systems that have developed in the archipelago. Therefore the NU tradition is the Nusantara tradition and NU Islam is Nusantara Islam, both of which are an inseparable unit, starting from tradition, custom, with all its heresies and superstitions. The scientific tradition of the Archipelago has been eroded in such a way by the Western knowledge system that came with the presence of colonialism, which from the beginning was persistent in studying tradition to master the spirit of that tradition, and then used it as a weapon to conquer the holders of the tradition. Various prodonances and systems were applied to wrap up the freedom of this nation, not only in the political and economic fields, but also shackled from the point of view of thought and science. They have defined language politics, spelling politics and transliteration politics are also implemented. One form of this tradition is silaturrahmi. There is a culture of friendship with relatives, both far and close, both those who are closely related to those who are far away, we visit, we visit their homes, they will connect with their feelings so that. As well as fostering feelings that touch each other. In the word of Allah subhanahu wa ta'ala, we have guests, we must respect our guests so that we are among those who believe in the Last Day, those who believe in the Last Day, of course, will do good to anyone because that is a threat. To maintain brotherhood. People who believe in the Last Day will collect and organize social actions with relatives and neighbors of guests that we need to respect when their children are guests of Allah that we need to respect and we should maintain the values of the religious teachings that we carry out during silaturrahim. Even in history Rasulullah saw when he had you Musailamah Al kadzab Rasulullah shallallahu'alaihi wasallam accompanied the group to his vehicle which was at a place some distance from Rasulullah's House. As well as giving memories or souvenirs to them. With the Messenger of Allah escorting his guests to their place to part with his guests as well as Rasulullah giving souvenirs to the guests who were present at the Prophet's house. We, as the people of the Prophet Muhammad Alaihissalam, we also respect guests the same as our uswah. The will to respect guests as well as the example of the Prophet sallallaahu alaihi wasallam, even the bad people and the Messenger of Allah are respected even though from the side of those who do not believe in the teachings of Islam and even distort the teachings of Islam, the Prophet still respects and builds social well.